PENGARUH STRES KERJA, INSENTIF DAN PELATIHAN TERHADAP MOTIVASI KERJA DI MASA PANDEMI COVID-19 - EKA WAHYUNI; SAIFUDDIN - (Jurnal Akademika, 2022)
The purpose of this study was to analyze: 1) the effect of partial work stress on employee work motivation, 2) the effect of partial incentives on employee motivation, 3) the effect of partial training on employee motivation, and 4) the effect of job stress, incentives and Simultaneous training on employee work motivation. The sample in this study amounted to 38 people. Data analysis techniques in this study include multiple linear regression analysis. The results showed that work stress had a negative and significant effect on employee motivation, incentives had a positive and significant effect on employee work motivation, training had an insignificant positive effect on employee motivation, and work stress, incentives and training simultaneously had a significant effect on employee work motivation.  Keywords: work stress, motivation, training, employee performance